ANALISA PROSES PRODUKSI PADA PROGRAM PEMBERITAAN KABAR SUMATERA DI TVONE BIRO MEDAN - Rizqi Ramadhani Siregar; Nadya Syakilah; Melda Wati Simanjuntak; Tasya Salsabila (Lembaga Pengembangan Kinerja Dosen, 2023)
In an era that is increasingly controlled by technology and information, it requires people to always know when sharing information. The mass media is one of the most important means of information in human life. The mass media currently playing a role in presenting information to the wider community is television. TvOne Medan Bureau is one of the TV One bureaus in North Sumatra. Precisely in the city of Medan. Through daily observations, TV One focuses on wrapping its various programs in the form of news. The research method used is qualitative research using a descriptive approach so that it emphasizes more on the understanding aspect of a problem. The descriptive approach focuses on the actual problem as it was at the time the research took place. In the pre-production stage, there are several stages, namely field data research, camera, lighting and audio. The production stage of the process of sending signals to various locations simultaneously. This process can be via satellite, radio, television and SNG cars. Lastly, post-production, at this stage the editing process will begin after everything is okay, it will be broadcast every Friday at 10.00 am.